The IRA on film and television a history - Connelly, Mark, 1951- (McFarland & Co., Inc., Publishers, 2012)
"The Irish Republican Army (IRA) has for decades pursued the goal of unifying its homeland into a single sovereign nation, ending British rule in North Ireland. This illustrated history analyzes celluloid depictions of the IRA from the 1916 Easter Rising to the peace process of the 1990s"--Provided by publisher.